Grippe, Pest und Cholera : eine Geschichte der Seuchen in Europa - Vasold, Manfred 1943- (Steiner, 2008)
About various epidemics in Europe including: Plague, smallpox, cholera, influenza, AIDS, tuberculosis, malaria, leprosy, typhus fever and sexually transmitted diseases including syphilis